2021
DOI: 10.1371/journal.pone.0253605
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-communicable diseases risk factors and their determinants: Results from STEPS survey 2019, Nepal

Abstract: Background The World Health Organization (WHO) recommends ongoing surveillance of non-communicable diseases (NCDs) and their risk factors, using the WHO STEPwise approach to surveillance (STEPS). The aim of this study was to assess the distribution and determinants of NCD risk factors in Nepal, a low-income country, in which two-thirds (66%) of annual deaths are attributable to NCDs. Methods A nationally representative NCD risk factors STEPS survey (instrument version 3.2), was conducted between February and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 30 publications
9
41
4
Order By: Relevance
“…A population-based cross-sectional study was carried out from February to May 2019 using a WHO STEPS survey, further details on methodology can be found elsewhere [ 11 ]. The survey population includes men and women aged 15–69 years who have been living at their place of residence for at least six months, although visitors who stayed in the households the night before the survey were also eligible for interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A population-based cross-sectional study was carried out from February to May 2019 using a WHO STEPS survey, further details on methodology can be found elsewhere [ 11 ]. The survey population includes men and women aged 15–69 years who have been living at their place of residence for at least six months, although visitors who stayed in the households the night before the survey were also eligible for interview.…”
Section: Methodsmentioning
confidence: 99%
“…The population prevalence of NCDs in Nepal has been found to be high, with 11.7% suffering from COPD (11.7%), diabetes mellites (8.5%), chronic kidney disease (6%) and coronary artery diseases (3%) [ 9 ]. The 2019 World Health Organization (WHO) STEPwise approach to surveillance of non-communicable disease risk factor (STEPS) survey reported almost 24.5% of the Nepalese population had raised blood pressure [ 10 , 11 ]. This is concerning, in particular as hypertension and CVDs have been found to place a large economic burden, arising from increasing health-care costs, lowering workplace productivity, increasing sick days, and inflicting permanent disability, on the country [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One participant per household was selected for the survey. The detailed methodology has been presented elsewhere 33–35…”
Section: Methodsmentioning
confidence: 99%
“…Smoking, coupled with a sedentary lifestyle (physical inactivity), is considered one of the major risk factors associated with non-communicable diseases. It is worth noting that not only do these factors foster the development of non-communicable diseases independently, but they also occur concurrently [ 9 , 10 ]. For instance, evidence has demonstrated an important negative association between physical exercise and risk for coronary heart disease such as angina, heart attack, heart failure, and abnormal heart rhythm [ 11 ], whilst a cohort analysis of US female nurses showed that PA, including moderate-intensity exercise such as walking, is correlated with a major reduction in the risk of stroke [ 12 ].…”
Section: Introductionmentioning
confidence: 99%